MinION nanopore sequencing accelerates progress towards ubiquitous genetics in water research - Werner, D.; Acharya, K.; Blackburn, A.; Zan, R.; Plaimart, J.; Allen, B.; Mgana, S. M.; Sabai, S. M.; Halla, F. F.; Massawa, S. M.; Haile, Alemseged Tamiru; Hiruy, A.M.; et al. (MDPI, 2022)
In 2014, Oxford Nanopore Technologies (ONT) introduced an affordable and portable sequencer called MinION. We reviewed emerging applications in water research and assessed progress made with this platform towards ubiquitous genetics. With >99% savings in upfront costs as compared to conventional platforms, the MinION put sequencing capacity into the hands of many researchers and enabled novel applications with diverse remits, including in countries without universal access to safe water and sanitation. However, to realize the MinION’s fabled portability, all the auxiliary equipment items for biomass concentration, genetic material extraction, cleanup, quantification, and sequencing library preparation also need to be lightweight and affordable. Only a few studies demonstrated fully portable workflows by using the MinION onboard a diving vessel, an oceanographic research ship, and at sewage treatment works. Lower nanopore sequencing read accuracy as compared to alternative platforms currently hinders MinION applications beyond research, and inclusion of positive and negative controls should become standard practice. ONT’s EPI2ME platform is a major step towards user-friendly bioinformatics. However, no consensus has yet emerged regarding the most appropriate bioinformatic pipeline, which hinders intercomparison of study results. Processing, storing, and interpreting large data sets remains a major challenge for ubiquitous genetics and democratizing sequencing applications.